A timing recovery algorithm for filter-bank multicarrier wireless systems - Saccomando, C.; Luise, M.; Lottici, V.; Spalla, F. (2004 IEEE 59th Vehicular Technology Conference, 2004)
Filter bank (FB) multicarrier modulation exhibits several properties which make it an attractive approach not only for high speed copper wire communications networks but also for broadband wireless applications. In this paper, we derive a non data aided timing offset recovery algorithm for wireless FB-based systems. The estimator is based on a maximum likelihood approach and has a feedback loop structure. A number of proper simplifications make the problem tractable and allow us to reduce the computational complexity. The algorithm accuracy is examined by computer simulation for AWGN and frequency selective multipath channels showing a considerable robustness against frequency errors.